Detection of O25b-ST131 clone in extended spectrum beta-lactamase-producing E. coli from urinary tract infections in Mexico - Josefina Duran-Bedolla; Juan Téllez-Sosa; Ana María González-Villoria; Humberto Barrios-Camacho (Journal of Infection in Developing Countries)
Introduction: Escherichia coli has emerged as an important pathogen in urinary tract infections (UTIs) due to the rapid acquisition of antibiotic resistance genes. This enhances the ability of E. coli to colonize and creates therapeutic challenges within the healthcare system. This study aimed to identify the extended spectrum beta-lactamase (ESBL) and O25b-ST131 pandemic clones in E. coli isolated from two hospitals in Mexico.